Orthogonal high-density mapping with ventricular tachycardia isthmus analysis vs. pure substrate ventricular tachycardia ablation: A case–control study - Vázquez-Calvo, Sara; Garre, Paz; Sanchez-Somonte, Paula; Borras, Roger; Quinto, Levio; Caixal, Gala; Pujol-Lopez, Margarida; Althoff, Till; Guasch, Eduard; Arbelo, Elena; Tolosana, José Maria; Brugada, Josep; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Substrate based-ablation has become a successful technique for ventricular tachycardia (VT) ablation. High-density (HD) mapping catheters provide high-resolution electroanatomical maps and better discrimination of local abnormal electrograms. The HDGrid catheter is a HD catheter with the ability to map orthogonal signals on top of conventional bipolar signals, which could provide better discrimination of the arrhythmic substrate. By other hand, conventional mapping techniques as activation mapping, when possible, helps to identify the isthmus of the tachycardia. Aims: The purpose of this study was to compare clinical outcomes after using two different VT ablation strategies; one based on extensive mapping with HDGrid including VT isthmus analysis and one based on pure substrate ablation. Methods: Forty consecutive patients undergoing VT ablation with extensive HD mapping method in Hospital Clinic (November 2018-November 2019) were included. Clinical outcomes were compared with an historical cohort of 26 consecutive patients who underwent ablation using scar dechanneling technique before 2018. Results: The density of mapping points was higher in the extensive mapping group (2370.24±920.78 VS 576.45±294.46;p<0.001). After one year of follow-up, VT recurred in 18.4% of patients in the extensive mapping group vs. 34,6% in the historical control group (p=0.14), with a significantly greater reduction of VT burden: VT episodes (81.7±7.79% VS 43.4%±19.9%,p<0.05), antitachycardia pacing (99.45±2.29% VS 33.9±102.5%,p<0.001) and ICD shocks (99±4.5% VS 64.7±59.9%,p=0.02). Conclusions: The use of a method based on extensive mapping with HDGrid catheter and VT isthmus analysis allows better discrimination of the arrhythmic substrate and could be associated with a greater decrease in VT burden.